Implementasi Simple Multi Attribute Rating Technique untuk Menentukan Kelayakan Pengajuan Kredit Mobil - Sinaga, Dinda Wanti; Syah, Arridha Zikra; Saputra , Endra (Universitas Hamzanwadi, 2024)
Increasing consumer demand for car loans requires finance companies to make quick and accurate decisions, so there are obstacles such as sufficient time in deciding whether to accept or reject loan applications by consumers. The purpose of this study is to create a decision support system using the simple multi-attribute rating technique (SMART) to assist in determining the feasibility of car loans. This study used a quantitative approach. The system built applies a waterfall model with stages of analysis, design, implementation, and testing. The analysis is carried out to find the needs of the system created, with design using UML, including class diagrams, entity relationship diagrams, and interface design. The implementation phase was carried out at Indomobil Finance Kisaran using consumer sample data from observations and interviews. System testing uses black box testing to see the performance of the system created. Our findings are that there need to be improvements to the data processing process and the duration of time for making decisions on accepting or rejecting car loans submitted by consumers. From the results of black box testing, no system failure was found, so the system is designed to run well and by expectations is to help the company determine the feasibility of car loans submitted by consumers with fast and accurate results.